(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents Comparison and Validation of Optimal path lengths in the presence of Elliptical Forbidden Regions between CGA and V-Rep simulation software. A systematic approach was made for developing results by applying a suitable CGA methodology that meets the solution requirements of routing problems that involve path planning procedures. CGA technique helps in reducing the evaluation time and also directly generates the shortest path for navigation to reach its destination point. The solutions thus obtained by CGA Technique absolutely agreed with the solutions by V-Rep and even produced optimal solutions when compared with V-Rep.